Textural and sensory properties and gel microstructure of set-yoghurt made of indigenous and exotic cow milk - Weerasingha, W.V.V.R.; Ranadheera, C.S.; Prasanna, P.H.P.; Silva, G.L.L.P.; Vidanarachchi, J.K. (University of Jaffna, 2022)
Distinctive milk composition variations have been identified among indigenous cattle and high-yielding exotic cattle breeds. A better milk compositional profile leads to dairy products with enhanced technological and functional properties. The current study was performed to assess the textural, microstructural and sensory properties of set-yoghurts produced using milk from two indigenous cattle types (Thamankaduwa White [TW] and Lankan cattle [LC]) and two exotic cattle breeds [Friesian and Jersey]. Set-yoghurts were made by inoculating commercial starter cultures composed of Streptococcus thermophilus, Lactobacillus delbrueckii ssp. bulgaricus and Bifidobacterium animalis ssp. lactis (BB-12). Instrumental texture profiles and scanning electron micrographs (SEM) of set-yoghurts during 21 days of refrigerated (4±1℃) storage were evaluated. Sensory attributes were evaluated with 40 untrained panelists using a five-point hedonic scale. Set-yoghurts made from indigenous cow milk showed higher (p<0.05) firmness, cohesiveness and apparent viscosity compared to those prepared using exotic cow milk. As revealed by micrographs, set-yoghurts made from TW milk had fewer and smaller void spaces and a dense protein gel network, while gel made from Friesian cow milk resulted in a weaker gel than the other milk gel types. The sensory analysis revealed that set-yoghurts made of TW milk had the highest (p<0.05) sensory scores for all sensory attributes, while set-yoghurts made of Friesian milk had the lowest (p<0.05) sensory acceptance. Overall results suggest the importance of using indigenous cow milk in producing set-yoghurts. These approaches may also provide a promising way to strengthen indigenous cattle farming, avoiding the genetic erosion of valuable indigenous breeds.
Keywords: Firmness; Instrumental texture; Sensory analysis; Viscosity